Novel Mechanisms of Exercise-Induced Cardioprotective Factors in Myocardial Infarction - Guo, Yuan; Chen, Jingyuan; Qiu, Haihua (Frontiers in Physiology, 2020)
Exercise training has been reported to ameliorate heart dysfunction in both humans and animals after myocardial infarction (MI). Exercise-induced cardioprotective factors have been implicated in mediating cardiac repair under pathological conditions. These protective factors secreted by or enriched in the heart could exert cardioprotective functions in an autocrine or paracrine manner. Extracellular vesicles, especially exosomes, contain key molecules and play an essential role in cell-to-cell communication via delivery of various factors, which may be a novel target to study the mechanism of exercise-induced benefits, besides traditional signaling pathways. This review is designed to demonstrate the function and underlying protective mechanism of exercise-induced cardioprotective factors in MI, with an aim to offer more potential therapeutic targets for MI.